Geopolitik dan geostrategi dalam mewujudkan integritas Negara Kesatuan Republik Indonesia - azhar, safa salsabila (Maliki Interdisciplinary Journal, 2026)
Indonesia is an archipelagic country with rich social and cultural diversity. This condition provides opportunities for Indonesia to become a strong maritime nation, but it also presents challenges to the integrity of the Unitary State of the Republic of Indonesia. By understanding the characteristics of the archipelagic region, geopolitical threats, and the strengthening of national resilience, this article discusses the role of geopolitics and geostrategy in maintaining the integrity of the Republic of Indonesia. This study uses a descriptive qualitative method with a literature study approach. Data were obtained from relevant literature, including books, journal articles, and scientific documents discussing geopolitics, geostrategy, the Archipelagic Outlook, national resilience, and the integrity of the Republic of Indonesia. The results show that the perspective of the Archipelagic Outlook integrates land, sea, air, and society as part of Indonesian geopolitics. Meanwhile, national resilience, which includes ideology, politics, economy, socio-culture, defense, and security, forms Indonesia’s geostrategy. Social tolerance, equitable development, maritime security, strengthening border areas, and national awareness are several efforts that can strengthen the integrity of the Republic of Indonesia. Therefore, geopolitics and geostrategy play an essential role in shaping thought and action to maintain Indonesia’s sovereignty, unity, and national integrity.